Complex linkages between forced labor slavery and environmental decline in marine fisheries. Issue 2 (15th March 2019) - Decker Sparks, Jessica L.; Hasche, Leslie K.
Abstract: Recent media attention on human rights abuses in the fishing sector, precipitated by undercover investigations from nongovernmental organizations and investigative journalists (e.g., Environmental Justice Foundation [EJF]2014, 2015a, 2015b ; Mendoza, McDowell, Mason, and Htusan2016 ), has prompted calls from the scientific community for increased transdisciplinary and empirical research of fisheries' social dimensions, such as labor (Kittinger et al.2017 ). Given views that social and ecological systems are interdependent (Ostrom2009 ), the need for theory development to explicate pathways for how this interdependence occurs and the potential for using policy and practices for intervention and prevention exist. Integrating ecological data and economics and human rights theory, Brashares and colleagues' (2014) wildlife decline and social conflict framework offered a hypothesis about the negative association between fish stock declines and child slavery. Yet, more precision in terminology, pathways, and feedbacks may be warranted. With the aim of exploring empirical, conceptual, and theoretical support for Brashares et al.'s (2014 ) pathways, the revised theory developed in this article posits how forced labor slavery and environmental decline in marine fisheries may be linked.